Daya Tahan Hidup Pseudomonas putida Strain Pf-20 dalam Beberapa Macam Inokulum - Yenny Wuryandari; Triwidodo Arwiyanto; Bambang Hadisutrisno; I. Hartana (Universitas Gadjah Mada, 2004)
For any crop-protection agent, an efficient formulation is a necessity to translate laboratory activity into adequate field performance. There are particular challenges to be faced in formulation of biological control agents, because the active ingredient is a living organism that must be kept relatively immobile and inactive while in storage, but quickly resume its normal metabolic processes once applied to the target site. The objective of the research was to study survival of Pseudomonas putida strain Pf-20 in various formulations at the storage time and germination. The twelve formulations include carriers, additives and concentration of Pf-20. The efficacy of various formulation in maintaining the population of Pf-20 in storage was assessed. The research result showed that population of Pf 20 in the formulation number seven was the highest, with the combination peat+talc, CMC+arginin and concentration of Pf[20 10^10 CFU/ml. In peat+talc, CMC+arginin, Pf-20 10^10 CFU/ml based formulation the bacteria survived even up to 84 days of storage although the population declined. In all formulations, population of Pf-20 increased at the time of seed germination. At the time of seed germination, formulation number seven was the highest too.